2021
DOI: 10.1016/j.celrep.2021.109309
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αvβ8 on T cells suppresses anti-tumor immunity in multiple models and is a promising target for tumor immunotherapy

Abstract: Integrin avb8 on T cells suppresses anti-tumor immunity in multiple models and is a promising target for tumor immunotherapy Graphical abstract Highlights d ITGB8 on CD4+/CD25+ T cells activates latent TGF-b, causing tumor immunosuppression d Anti-ITGB8 therapy elicits tumor regression and durable antitumor immunity d CD8+T cells are essential for anti-tumor activity of anti-ITGB8 d Anti-ITGB8 synergizes with multiple immunomodulators in multiple tumor types

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…While data presented here suggest that therapeutics blocking α V β 8 integrin’s ability to activate TGF-β have great promise in preventing fibrotic PCO, unanswered questions remain. First, the function blocking antibody therapy used in this study was administered to the animals intravenously as the systemic administration of ADWA-11 showed no evidence of toxicity in prior studies ( 34 , 56 , 57 ), and a humanized version of ADWA-11 did not elicit notable systemic toxicity in mice and Cynomolgus monkeys treated for over 1 month at doses more than 5 times that used here ( 56 , 57 ). However, attempts to directly inject the ADWA-11 into the mouse capsular bag at surgery did not block the fibrotic transformation of LCs.…”
Section: Discussionmentioning
confidence: 86%
“…While data presented here suggest that therapeutics blocking α V β 8 integrin’s ability to activate TGF-β have great promise in preventing fibrotic PCO, unanswered questions remain. First, the function blocking antibody therapy used in this study was administered to the animals intravenously as the systemic administration of ADWA-11 showed no evidence of toxicity in prior studies ( 34 , 56 , 57 ), and a humanized version of ADWA-11 did not elicit notable systemic toxicity in mice and Cynomolgus monkeys treated for over 1 month at doses more than 5 times that used here ( 56 , 57 ). However, attempts to directly inject the ADWA-11 into the mouse capsular bag at surgery did not block the fibrotic transformation of LCs.…”
Section: Discussionmentioning
confidence: 86%
“… 32 More interestingly, ITGB8 functions as a key driver of transforming growth factor b (TGF-b) to impede the antitumor immunity leading to the tumor growth. 33 …”
Section: Resultsmentioning
confidence: 99%
“…Recently, a study demonstrated that upregulation of integrin β8 mediated by lnc-TCF7 leads to ovarian cancer stemness ( 190 ). Integrin αvβ8, a key activator of TGF-β, regulates immunotherapy and radiotherapy resistance, which may be reversed by a potent blocking monoclonal antibody against integrin αvβ8 (ADWA-11) in prostate cancer ( 191 ). The anti-integrin β8 antibody treatment mechanism restores the in vitro cytotoxic effect of tumor CD8 T cells by inhibiting Treg cells ( 191 , 192 ).…”
Section: Integrin and Endocrine-related Cancersmentioning
confidence: 99%